Perjumpaan antara Teologi dan Antropologi: Memeriksa Shamanisme, Kristianitas, dan Alam di Asia Tenggara - Ngu, Kai (Indonesian Journal of Theology, 2025)
Inspired by Joel Robbins’s call for theology and anthropology to collaborate as theoretical partners, in this article, I examine the theologian Jojo M. Fung’s recent books, Sacred Sustainability, Polyhedral Christianity and Cosmic Challenges (2025) and A Shamanic Pneumatology in a Mystical Age of Sacred Sustainability (2017) from the point of view of an anthropologist. In these books, Fung builds a theoretical bridge to connect the Creative Spirit in the creation narratives of Genesis to spirits of nature in indigenous religious practices, in what he calls “creational pneumatology.” I argue that Fung’s theological engagement with indigenous religious communities in Southeast Asia illuminates the secular assumptions of the “more-than-human” turn in anthropology and beyond, and how such a turn remains inextricably tied to the “human” even in attempts to exceed it. Yet, I also point out that theologians like Fung can benefit from anthropology’s epistemic tools in explicitly highlighting how one’s interpretive lens colors one’s perception of the Other. Orchestrating this interdisciplinary dialogue between theology and anthropology illuminates the premises and assumptions embedded in each discipline, which will ultimately sharpen their respective aims.